Translanguaging in the analysis of narrative techniques and discourse styles in selected Philippine short novels - Esnara, Chester B. (Research Journal in Advanced Humanities, 2022)
This research undertook an innovative approach to the language-literature interface by means of adopting a modified model of translanguaging in the analysis of the narrative techniques and discourse styles of three selected Philippine short novels: Getting Better by Tara F. Sering, What Things Mean by Sophia N. Lee, and Salingkit by Cyan Abad-Jugo. Theories on language and thought and the modularity of the mind were reviewed in the reconfiguration of the translanguaging model assisted by CDA and the protocol of discourse analysis particularly in the gathering and treatment of data. Results of the study indicated the effectiveness of translanguaging strategies emanating from the aesthetic translanguaging space and the imaginative translanguaging instinct of the authors which helped in the appealing narrative techniques and creative discourse styles of the works. It is recommended that translanguaging as practice and theory be explored further in ESL/ELT/EMI and the disciplines to optimize its potentialities as a decolonizing stance as well as a relevant and helpful paradigm in resolving pressing language-related problems and challenges of the times.